Integrating Volleyball Play into Elementary Science Learning: A Contextual Approach to Understanding Projectile Motion Concepts - Sumarjo Sumarjo; Muhammad Saiful (Journal of Innovation and Research in Primary Education, 2026)
This study examines the effectiveness of integrating volleyball play into elementary science instruction as a contextual and embodied approach to improving students’ conceptual understanding of projectile motion. A quasi-experimental non-equivalent control group design was employed involving 60 fifth-grade students from an Indonesian public elementary school, divided into an experimental group receiving volleyball-based instruction and a control group receiving conventional instruction. Conceptual understanding was assessed using a validated two-tier test, along with student engagement surveys and observations of implementation fidelity. Results indicated that the experimental group achieved significantly higher posttest scores (M = 82.67, SD = 6.91) than the control group (M = 68.40, SD = 8.14), with a medium–high normalized gain (N-Gain = 0.68) compared to the control group (N-Gain = 0.43). ANCOVA results confirmed a significant effect of the instructional approach on posttest performance after controlling for pretest differences, F(1,57) = 28.89, p < .001, partial η² = .334, indicating a large effect size. Student engagement levels were also significantly higher in the experimental group across the attention, participation, and enthusiasm dimensions (p < .01). These findings suggest that embedding structured physical play into science instruction is an effective pedagogical strategy for enhancing both conceptual understanding and engagement in elementary physics learning.